Critical Analysis of the Implementation of the Independent Curriculum in Islamic Religious Education Learning - Marleni Marleni; Lydia Meliana Sari; Muhamad Yusron Zakya (LP3M Pascasarjana STAI Ibnurusyd, 2026)
The Merdeka Curriculum is a transformative policy introduced by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, which has been implemented gradually since 2022. This policy brings a new paradigm to the field of education, including the subject of Islamic Religious Education (PAI). This study aims to critically analyze how the implementation of the Merdeka Curriculum takes place in PAI learning in schools and madrasahs, with particular attention to teacher readiness, shifts in learning paradigms, the application of instructional differentiation, and its impact on students’ character development.The method used in this study is a qualitative literature review with an analytical-critical approach toward various scientific sources, including national and international journal articles, government policies, and field research reports published between 2019 and 2024. The findings indicate that the Merdeka Curriculum provides greater flexibility for PAI teachers to design contextual, project-based learning oriented toward the development of the values embodied in the Pancasila Student Profile: faith in and devotion to God Almighty, and noble character.However, its implementation still faces several significant challenges, including limited digital literacy among teachers, inadequate training opportunities, infrastructure disparities between regions, and cultural resistance to changes in pedagogical approaches. Theoretically, the Merdeka Curriculum is aligned with the principles of humanistic Islamic education, which emphasize the holistic development of human potential (fitrah). This study recommends strengthening the capacity of PAI teachers on an ongoing basis, providing locally based teaching modules, and fostering synergy among the government, Islamic higher education institutions, and madrasah communities in ensuring the effective and meaningful implementation of this curriculum.